Theology and the fragmentation of the ummah : towards a theology of unity - Ssekamanya, Siraje Abdallah (ISTAC, 2012)
How did Muslims get fragmented and what should we do to rekindle the spirit of unity among them? This paper, after reviewing the nature and development of Sunni Muslim theological thought, argues that the way forward lies in adopting a new approach to theological discourse, akin to that used by the jurists, in what one might call “a theology of unity,” which is the true spirit of tawhid.